PEMBERIAN AIR KELAPA MUDA UNTUK PENURUNAN NYERI HAID PADA STAF PUSKESMAS HUTABARGOT MANDAILING NATAL - Herri Novita Tarigan; Megawati Sinambela (INSTITUT KESEHATAN DELI HUSADA, 2021)
Dismenorhoe is a medical condition that occurs to menstruation that can interfere with activity and requires treatment characterized by pain or pain in the abdomen or pelvis . Menstruation is periodic bleeding and cycles from the uterus , accompanied by the release or dedeconstruction of the endometrium that occurs every month regularly in mature and healthy women . The purpose of this study is to find out if there is an